Single route formation of doped polyaniline/ porous silicon heterojunction - Lozada, Lou Serafin M.; Ramos, Henry J. (Quezon City National Institute of Physics, College of Science, University of the Philippines Diliman, 2009)
Polyaniline and porous silicon heterostructure was fabricated using direct current plasma enhanced chemical vapour deposition. Porous layer was obtained by subjecting silicon surface to argon glow discharge. Polymerization and deposition of polyaniline on silicon were performed in three methods: aniline with and without argon polymerized on untreated silicon, and aniline with argon on porous silicon. Silicon surface was modified by argon plasma resulting to formation of submicron pore and cone structures.
Thesis (M.S.Physics)--University of the Philippines Diliman
Keywords: Polyanilines; Porous silicon; Chemical vapor deposition